Coping with HIV/AIDS-Related Stigma and Discrimination: An Overview Based on a Personal Loss - Călinescu, Amalia (Integrated Journal for Research in Arts and Humanities, 2023)
Stigma and discrimination have a profound psychological and societal impact on individuals living with HIV/AIDS and their communities. This research offers an in-depth exploration of these challenges, drawing insights from a vast array of sources, such as articles, books, films, documentaries, websites, reports, resolutions, and famous stories. In order to provide valuable insights into building resilience and fostering supportive environments, the study simultaneously examines the coping mechanisms and strategies employed by the infected, as depicted in the literature used therein. The example of Miha, a young woman who faced societal biases despite her achievements, serves as a poignant reminder of the many sad narratives behind the statistics. This paper ultimately emphasizes the urgent need for continued efforts in awareness, education, and advocacy of combating HIV/AIDS-related stigma and discrimination, and culminates in a call for collective action, empathy, and a shared vision of an inclusive world.